The Supporting Role of Physiotherapy and Nursing in Promoting Patient Compliance with Rehabilitation Programs - Al Dossari, Waad Muslim; Hakami, Zahra Hamad; Mhnashi, Ageela Abutaleb Ali; Alasmari, Hassan Mousa Mohammed; Alasmari, Hassan Mohammed Ali; Alahmari, Amer Mohammed Amer; Alsharif, Hana Ahmed Mohammed; Alshehah, Munirah Mohammed; Alsaleh, Anwar Saleh; Alalhareth, Ibrahim Khudaysh Hameed; Alawlah, Bshayer Khalid; Alotaibi, Wadha Sharar; et al. (Journal of Ecohumanism, 2024)
Achieving optimal outcomes in rehabilitation is contingent on patient adherence to prescribed rehabilitation programs. Non-compliance with rehabilitation protocols is a significant barrier to recovery, and it can result in extended recovery periods, worsened conditions, or even permanent impairment. Successful rehabilitation hinges on a multifaceted approach, where interdisciplinary collaboration plays a critical role in fostering patient compliance. Nursing specialists, nurses, nursing technicians, technician-midwifery professionals, physiotherapists, and physical therapists each bring distinct skills and knowledge to the rehabilitation process, ensuring that patients remain engaged, motivated, and consistent in following rehabilitation instructions. This article explores the multifactorial aspects of patient compliance, emphasizing the supporting roles of different healthcare professionals and how their collaborative efforts can improve patient adherence to rehabilitation programs. Through communication, patient education, emotional support, and customized interventions, these professionals contribute significantly to the promotion of patient compliance, ultimately leading to better rehabilitation outcomes.